Bacterial dynamics and functions for gaseous emissions and humification in response to aeration intensities during kitchen waste composting - Xu, Zhicheng; Qi, Chuanren; Zhang, Lanxia; Ma, Yu; Li, Jungang; Li, Guoxue; Luo, Wenhai (Bioresource technology, 2021)
[Display omitted] •Aeration intensity notably altered bacterial dynamics in kitchen waste composting.•Aeration increase inhibited functional bacteria to reduce GHG and H2S emissions.•Aeration increase enriched thermophilic bacteria to accelerate organic degradation.•Enhanced organic biodegradation favoured NH3 emission and humus precursor formation.•Humus precursors were further mineralised to reduce humification at high aeration. This study revealed bacteria dynamics and functions for gaseous emissions and humification during kitchen waste composting under different aeration intensities (i.e. 0.24, 0.36, and 0.48 L kg−1 DM min−1) using high-throughput sequencing with Functional Annotation of Prokaryotic Taxa. Results show that aeration increase restrained bacteria (e.g. Lactobacillus and Acinetobacter) for fermentation, nitrate reduction, and sulphur/sulphate respiration, but enriched thermophilic bacteria (e.g. Thermomonospora and Thermobifida) for aerobic chemohetertrophy, xylanolysis, cellulolysis, and methylotrophy. Thus, high aeration intensity (i.e. above 0.36 L kg−1 DM min−1) effectively alleviated the emission of greenhouse gases and hydrogen sulphide, and meanwhile facilitated the production of humus precursors and ammonia. Nevertheless, humification was limited by the conclusion of composting under high aeration conditions due to the consumption of humus precursors for bacterial activity. Thus, aeration intensity should be regulated at different stages indicated by temperature to balance gaseous emissions and humification during kitchen waste composting.